Ivan Pavlov : a Russian life in science - Todes, Daniel Philip (Oxford University Press, 2014)
"Using a wide variety of previously unavailable archival materials, Todes tells a vivid story of that life and redefines Pavlov's legacy. Pavlov was not, in fact, a behaviorist who believed that psychology should address only external behaviors; rather, he sought to explain the emotional and intellectual life of animals and humans, "the torments of our consciousness." This iconic "objectivist" was actually a profoundly anthropomorphic thinker whose science was suffused with his own experiences, values, and subjective interpretations. Todes's story of this powerful personality and extraordinary man is based upon interviews with surviving coworkers and family members (along with never-before-analyzed taped interviews from the 1960s and 1970s), examination of hundreds of scientific works by Pavlov and his coworkers, and close analysis of materials from some twenty-five archives. The materials range from the records of his student years at Riazan Seminary to the transcripts of the Communist Party cells in his labs, and from his scientific manuscripts and notebooks to his political speeches; they include revealing love letters to his future wife and correspondence with hundreds of scholars, artists, and Communist Party leaders; and memoirs by many coworkers, his daughter, his wife, and his lover"--Publisher's description.